Psychological Effects of the Transition to Retirement - Osborne, John W. (Canadian Journal of Counselling and Psychotherapy, 2011)
Psychological effects of disengagement from a work life and the transition to retirement are discussed. These effects include partial identity disruption, decision paralysis, diminished self trust, experience of a post retirement void, the search for meaningful engagement in society, development of a retirement/life structure, the confluence of aging and retirement, death anxiety, the critical nurturing of social relationships, and self-actualization. Some aspects of preretirement life that can be predictive of a successful transition are also presented. This article is relevant for both counsellors and retirement advisors, whose clients may be planning retirement or have retired.